Efektifitas terapi kombinasi jus bayam dan tomat terhadap peningkatan kadar hemoglobin Pada ibu hamil dengan anemia - Novie - Merida; Misrawati - -; Wasisto - Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research is to analize the effectiveness of the combination of spinach and tomatoes juice therapy towards elevated levels of hemoglobin for pregnant women with anemia. The research used quasy experiment design with non-equivalent control group which is divided into experimental group and control group. The research was conducted on pregnant women in the “Puskesmas Sail Pekanbaru”. The sample of this research is taken by using purposive techniques sampling which is selected based on inclusion criteria. The instrument of this research used Easy Touch digital levels of hemoglobin gauges. Data then analyzed into univariate and bivariate with use independent and dependent sample t test. The results showed that therapy combination of spinach and tomatoes juice is effective towards elevated levels of hemoglobin for pregnant women in anemia with p value (0,013) < α (0,05). The results of this research recommend every health care to give education and promotion about complementary therapy for pregnant woment especially combination therapy of spinach and tomatoes juice. Key words: anemia, hemoglobin levels, pregnant women, spinach juice, tomatoes juice.